Impact of nutrition education on nutritional knowledge and intentions towards nutritional counselling in Dutch medical students: an intervention study - Hester L Coppoolse; Jaap C Seidell; S Coosje Dijkstra (BMJ Open)
Objective Management of diet-related chronic diseases may benefit from improved nutrition education of medical students. This study aims to investigate the effects of a nutrition education course on nutritional knowledge and intentions towards nutritional counselling in Dutch medical students.Design This is a pre–post intervention study with a comparison group. Participants completed self-reported questionnaires on nutritional knowledge and intentions towards nutritional counselling.Participants In total, 118 medical students (64.4% undergraduate, 73.2% women) were recruited from two medical schools in the Netherlands (n=66 intervention group, n=52 comparison group).Intervention The intervention group completed a 25-hour course in nutritional counselling (the Students Experienced in Lifestyle and Food (SELF) course) in addition to the standard medical curriculum. The comparison group followed the standard medical curriculum.Outcome measures Self-reported nutritional knowledge and intentions towards nutritional counselling, including attitude, self-efficacy and social support.Results Nutritional knowledge (B: 2.42, 95% CI 1.81 to 3.02), attitude in men (B: 0.50, 95% CI 0.13 to 0.87) and self-efficacy (B: 0.78, 95% CI 0.62 to 0.95) significantly increased in the intervention group compared with the comparison group. No significant differences were found for social support (B: 0.20, 95% CI −0.02 to 0.43) and attitude in women (B: 0.08, 95% CI −0.24 to 0.31) between the two groups.Conclusions The SELF course increased medical students’ nutritional knowledge and stimulated their intentions towards nutritional counselling. Future research is needed to evaluate the long-term impact of nutrition education interventions on physician practice patterns and patient outcomes.